The Revised Academic Consensus Definition of Terrorism - Alex P. Schmid (Perspectives on Terrorism)
Terrorism is a contested concept. While there are many national and regional definitions, there is no universal legal definition approved by the General Assembly of the United Nations (the one proposed by the Security Council in Res. 1566 (2004) is non-binding, lacking legal authority in international law). The Ad Hoc Committee on Terrorism of the 6th (legal) Committee of the General Assembly has, with some interruptions, been trying to reach a legal definition since 1972 - but in vain. In the absence of a legal definition, attempts have been made since the 1980s to reach agreement on an academic consensus definition. The latest outcome is the revised definition reprinted below. It is the result of three rounds of consultations among academics and other professionals. A description how it was arrived at can be found on pp. 39 - 98 of Alex P. Schmid (Ed.). The Routledge Handbook of Terrorism Research. London and New York: Routledge, 2011. The same volume also contains 260 other definitions compiled by Joseph J. Easson and Alex P. Schmid on pp. 99 -200.